Moderating effects of transformational leadership between external team learning and research team performance outcomes. (2nd September 2014) - Peltokorpi, Vesa; Hasu, Mervi
<x xml:space="preserve">Abstract</x> A growing body of empirical research examines the effects of external team learning on team performance. While previous studies suggest that external learning activities enhance team performance, the contingencies of such activities have received less research attention. This study examines the moderating effects of transformational team leadership between external team learning and two team performance outcomes: (1) accepted and published articles in peer‐reviewed scientific journals, and (2) project occupancy rate. The study was conducted with 124 research teams. Supporting the hypotheses, the findings show that transformational leadership has a positive moderating effect between external team learning and both team performance outcomes.